The fourth turning is here : what the seasons of history tell us about how and when this crisis will end - Howe, Neil (Simon & Schuster, 2023)
"The visionary behind the bestselling phenomenon The Fourth Turning looks once again to America's past to predict our future in this startling and hopeful prophecy for how our present era of civil unrest will resolve over the next ten years--and what our lives will look like once it has"--